Digital-Based UMKM Branding & Marketing Innovation Assistance for Rengginang and Shrimp Cracker Businesses - Rokhmatulloh, Nur; Anwar, Khoirul; Hidayat, Nur (Amalee: Indonesian Journal of Community Research and Engagement, 2024)
Throughout the decade of increasingly rapid digital growth, digital technology has been one of the needs and has played a major role in innovating branding and marketing of micro, small, and medium enterprises (MSMEs) in various sectors. Digitalization is part of the development and innovation to change traditional branding and marketing into digital-based marketing in Rengginang and Krupuk Udang businesses. The purpose of community service activities through mentoring the community is to provide insight and skills about product digitalization in the form of labeling and marketing so that the community can innovate and develop products, especially to improve the welfare of the community in Gerongan Village, Kraton District, Pasuruan Regency. The ABCD (Asset Based Communities Development) method is the community service Method, which is structured and based on the needs and potential to develop village communities. The following are the steps used: Local Identification and Analysis (Discovery), Brand Identity Development (Dream), Optimization of Production Practices and Product Quality (Define), Use of Digital Technology and Marketing (Destiny), and Performance Measurement and Evaluation. The results of this community service activity indicate an increase in MSME insight into the importance of digital-based branding innovation and digital marketing, increasing labeling skills, and digitalization of marketing for innovation and development in their businesses.